2013
DOI: 10.1021/jo402155b
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Off-Cycle Species in the Acid-Catalyzed Aza-Piancatelli Rearrangement

Abstract: The observed rate of reaction in the dysprosium triflate catalyzed aza-Piancatelli rearrangement is controlled by a key off-cycle binding between aniline and catalyst. Deconvoluting the role of these ancillary species greatly broadens our understanding of factors affecting the productive catalytic pathway. We demonstrate that the rate of reaction is controlled by initial competitive binding between the furylcarbinol and nitrogen nucleophile using either a Brønsted or Lewis acid catalyst and that the resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…However, during the course of our investigations (Scheme ), we became aware that there was room for improvement because of some issues that still needed to be addressed: i) potential side‐reactions such as Friedel–Crafts or deoxyamination reactions, ii) a possible decomposition of the furylcarbinol through its intermediate oxonium at high temperatures, iii) the lower reactivity of anilines bearing electron‐donating groups, and iv) the absence of reactivity with the more basic alkylamines. In the last case, Hein and co‐workers pointed out that this problem might be explained by the generation of an “off‐cycle species” between the amine and the Lewis acid, which would limit the rate of reaction ,. This deleterious effect is actually not only encountered with alkylamines, but also with anilines substituted by electron‐donating groups.…”
Section: Introductionmentioning
confidence: 99%
“…However, during the course of our investigations (Scheme ), we became aware that there was room for improvement because of some issues that still needed to be addressed: i) potential side‐reactions such as Friedel–Crafts or deoxyamination reactions, ii) a possible decomposition of the furylcarbinol through its intermediate oxonium at high temperatures, iii) the lower reactivity of anilines bearing electron‐donating groups, and iv) the absence of reactivity with the more basic alkylamines. In the last case, Hein and co‐workers pointed out that this problem might be explained by the generation of an “off‐cycle species” between the amine and the Lewis acid, which would limit the rate of reaction ,. This deleterious effect is actually not only encountered with alkylamines, but also with anilines substituted by electron‐donating groups.…”
Section: Introductionmentioning
confidence: 99%
“…e l s e v i e r . c o m / l o c a t e / t e t a 4p electrocyclic ring closure of a pentadienyl cation (D), 4 analogous to the Nazarov cyclization. 5 Some of the current drawbacks with the Piancatelli rearrangement are the use of stoichiometric quantities of Brønsted or Lewis acid, the product is often isolated in low yield (40e55%), and the acid catalyzed reaction can result in the formation of polymeric material that may be difficult to remove, especially on scale.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…The resulting reaction mixture was heated to 80 C for 2 h. The reaction was then quenched with 1.5 mL of saturated aqueous sodium bicarbonate, diluted with 3 mL H 2 O, and extracted with diethyl ether (3Â7 mL). The combined organic layers were dried over MgSO 4 …”
Section: General Experimental Procedures A: Schemementioning
confidence: 99%
“…We proposed that rare earth metal salts bear large ionic radii and multiple-coordination manners, 13 which might be disadvantageous to create a tight pocket to conne the hydrocyclopentadienyl cation to deliver enantiocontrol in the competition of amine 2. 14 The existence of water generated in the rearrangement step will accelerate the formation of a poor-enantioselective OH-bridged dimer when indium(III) salt was used. 15 Aer examining other metal salts, we found that the reaction could be achieved with medium yield and enantioselectivity (36% yield, >19 : 1 dr, 65% ee; Table 1, entry 5) in the presence of Co(BF 4 ) 2 $6H 2 O, where the center metal ion Co(II) is so and bears a small ionic radius, reducing the bonding of the amine nucleophile and forming a suitable chiral pocket with the ligand to dene the stereochemistry in the rearrangement of the hydrocyclopentadienyl intermediate.…”
Section: Introductionmentioning
confidence: 99%